ChemInform Abstract: Synthesis and Ring Transformation of Oxygen and Nitrogen Spiro Bisheterocycles. Issue 24 (June 2015) - Talhi, Oualid; Pinto, Diana C. G. A.; Almeida Paz, Filipe; Hamdi, Maamar; Silva, Artur M. S.
Abstract: A facile and rapid access to various bridgehead spiro bisheterocycles based on spiro‐to‐spiro ring transformation of easily available spiro[chromanone‐hydantoin] compounds (I) is described.